Effects of increasing hydrostatic pressure on sinking diatom aggregates - Peter Stief; Clemens Schauberger; Kevin W Becker; Marcus Elvert; John Paul Balmonte; Belén Franco-Cisterna; Mathias Middelboe; Ronnie N Glud (PANGAEA, 2023)
The effect of increasing hydrostatic pressure on the microbial degradation, the organic matter composition, and the microbiome of extquotesinglemarine snow extquotesingle particles was studied in laboratory incubation experiments. Model aggregates were produced from the diatom Skeletonema marinoi and the natural microbial community of surface seawater collected in the Kattegat. The aggregates were incubated individually in rotating pressure and control tanks to keep them suspended during 20-day incubations in the dark and at 3°C. In the pressure tanks, hydrostatic pressure was increased at increments of 5 MPa per day to finally reach 100 MPa. This pressure scheme simulates the descent of diatom aggregates from the surface ocean down into a 10-km deep hadal trench. In the control tanks, pressure always remained at atmospheric level. Aerobic respiration was continuously measured as a proxy for oxidative carbon mineralization in the aggregates (Stief et al. 2021, https://doi.org/10.1002/lno.11791). Leakage of dissolved organic carbon was monitored as an additional carbon loss term. The contents of different diatom lipids and photopigments were measured throughout the incubation. The succession of microbial (mainly bacterial) communities associated with the sinking diatom aggregates was followed by 16S rRNA gene amplicon sequencing throughout the incubation; the corresponding data are deposited in the NCBI short-read archive under the accession number PRJNA976707.